Six Minute Walk Test as A Measurement Tool for Functional Capacity - Nusdwinuringtyas, Nury (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Various scientific articles which include scientific writing, books or journals have been known to provide evidence based scientific facts. Thus, in order to achieve accurate evidence based results, a clear outcome measurement is required. Besides, the measurement should be based on precise measurements, both in methods and tools utilized during the measurement. This is a very essential matter, as the accuracy of an outcome measurement would correlate to intervention, program and prognosis of an individual.